Physicochemical and Pharmaceutical Analysis of Swarnagairikadi Gutikanjana – An Ayurveda Herbomineral Formulation - Gujral, Mahima; Rajagopala, Manjusha (International Research Journal of Ayurveda & Yoga, 2021)
Eye is the most essential sense organ mentioned in Ayurveda. For the prophylactic as well as therapeutic purposes so many formulations are mentioned in Susruta Samhita for the eye and its disorders. One such formulation is Swarnagairikadi Gutikanjana. The preparatory procedure of such formulations needs authentication and standardization. Here modern day tools are applied for the pharmacognostical and pharmaceutical analysis which is necessary for scientific justification. The detailed analytical study helps in knowing the pharmacokinetics and pharmacodynamics of the formulation. The quality, efficacy, purity, and strength of the drug are also evaluated with the classical references of Rasashashtra. The analytical techniques of Rasashashtra as well as todays sophisticated qualitative and quantitative parameters are used in the processing of this formulation. The drug procurement, methodology of preparation and various parameters have been described in detailed manner with an objective of its reproducibility.